Utility of rotational thromboelastometry in total hip replacement revision surgery (case-control study). Issue 51 (18th December 2020) - Jonas, J.; Tomas, Vymazal; Broz, T.; Durila, Miroslav
Abstract : Abstract: Total hip replacement revision surgery is accompanied by significant blood loss. Using rotational thrombelastometry (ROTEM) perioperatively to diagnose coagulopathy may help to provide rapid aimed therapy and thus decrease blood loss and the consumption of transfusion products. The aim of this case-control study was to find out whether point of care using of ROTEM may reduce blood loss and the consumption of blood transfusion products in hip replacement revision surgery. Data were prospectively collected from patients who underwent hip replacement revision surgery in the period 2017 to 2018 when the management of bleeding and coagulopathy was based on the results of ROTEM. Data were compared with a group of historical controls for the period 2015 to 2016 when bleeding and coagulopathy management was not based on ROTEM results. The consumption of blood transfusion products and perioperative blood loss were compared between the groups. The total number of analyzed patients was 90. Forty five patients were analyzed in the ROTEM group and the same number of patients were analyzed in the non-ROTEM group. Significantly decreased perioperative consumption of fresh frozen plasma and packed red blood cells was found in the ROTEM, as well as decreased perioperative blood loss comparing to non-ROTEM group. All data were statistically different with P < .05. Perioperative management of bleeding and coagulopathy based on the results of ROTEM during hip replacement revision surgery seems to help to decrease perioperative blood loss and the consumption of blood transfusion products, especially fresh frozen plasma.